Alternative Tourism Development at Curug Ciherang - Annisa Pratiwi; kuncoro pribadi (Jurnal Sosial Humaniora Terapan, 2019)
This research aims to describe a form an alternative tourism based on the planning of tourist attraction and facilities, the local people's involvement in tourism activities, the object development strategy and supporting facilities and the role of stakeholders in developing tourism potential in Curug Ciherang. The findings were analyzed using qualitative descriptive analysis method, which is then presented as a narrative. This research was conducted in the scope of tourist attraction’s manager and local people. The research objects are limited to the tourism activities of the local people, facilities, and the development strategy of tourist attraction. These sample are taken by interviewing five respondents. The results show that the Curug Ciherang tourist attraction have the potential to be developed into the main tourist destination for it has a unique alternative tourism. However, there is still a need to be added to improve the competition with other tourist objects. Based on this research the author conclude is optimizing the potential that exist in Curug Ciherang as alternative tourism destination, the tourist attraction provides economic benefits to local people and building facilities to support the tourism activities in Curug Ciherang.